Herbal medicine for experimental type 2 diabetes and atherosclerosis - Białoszycka, Żanna; Biloshytska, Alina; Białoszycka, Monika Małgorzata; Pachevska, Alisa; Vasyliev, Mykyta (Quality in Sport, 2025)
Introduction. In the present era, atherosclerosis and type 2 diabetes represent the most socially significant diseases. Furthermore, the situation is exacerbated by the prevalence of chronic stress among the Ukrainian population. Among the organs most affected by this process, the liver is of particular significance. Aim. The objective of this study is to examine the impact of herbal preparations on the restructuring of liver tissue in the context of experimental atherosclerosis and diabetes. Materials and methods. The study was conducted on a group of 50 male rats. The classical model of atherosclerosis proposed by Anichkov and the dexamethasone suppression model of diabetes were employed in this study. A decoction of Transcarpathia medicinal plants (prepared according to our own recipe) was used as a prophylactic agent. Results. The experimental model of atherosclerosis and diabetes revealed the development of degenerative changes in the liver. These changes are most evident in the group that has undergone two simulated pathological processes. The prophylactic administration of traditional medicinal plants from Transcarpathia was observed to have a pronounced hepatoprotective effect. Conclusions. The experimental induction of atherosclerosis and diabetes in animals has been observed to result in degenerative alterations to the liver parenchyma and stroma. The prophylactic administration of a decoction of medicinal plants from Transcarpathia has been demonstrated to exert a hepatoprotective effect, as evidenced by morphological studies.